PARTISIPASI DAN KEAKTIFAN MAHASISWA PADA MATA KULIAH METODE PENELITIAN PENDIDIKAN I MENGGUNAKAN APLIKASI ZOOM MEETING - Sulistiana, Devita (Universitas Islam Balitar, 2022)
This study aims to determine the participation and activeness of students in attending the Education Research Method 1 course using the zoom application. The research method used is descriptive qualitative method. The population of this research is FKIP UNISBA Blitar students who are active in the second semester of the academic year following the Education Research Methods 1 course, the research sample is 38 people who were taken using purposive sampling. The results of data and data analysis, it is known that student learning participation reaches 88.33% with high criteria, while student learning activities from 4 aspects, namely speaking activity, listening activity, writing activity, and mental activity with an average percentage reaching 85.35 % with high criteria. From the aspect of learning activities, it is known in detail that the speaking aspect is 81.58%, listening activity is 83.99%, writing activity is 83.55%, motor activity is 89.47%, and mental activity is 88.16%. It can be concluded that the participation and activeness of students in the Education Research Method 1 course using the zoom meeting application showed very good results. It is necessary to increase students' communication skills in providing questions and responses to show student activity during lectures.